1980
DOI: 10.1159/000250487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous and Intracutaneous Bacillus Calmette-Guérin Application on the Drug-Metabolizing System of the Liver

Abstract: Both single intravenous and repeated intracutaneous injections of bacillus Calmette-Guérin (BCG) resulted in alteration of the hepatic microsomal drug-metabolizing enzymes of the rat liver. The cytochrome P-450 content was not significantly altered; its activity (ethoxycoumarin O-dealkylation) was inhibited in both the intravenous and intracutaneous group. The arylhydrocarbon-hydroxylase and aminopyrine-demethylase activities were also diminished; decrease of cytochrome-c-reductase activity was noted after int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…These inflammatory mediators released from granulomatous reaction inhibit the de novo synthesis of enzymes in the endoplasmic reticulum of the hepatocytes. This is consistent with previous work where BCG significantly reduced drug biotransformation in animals (14,15). Moreover, Farguhar et al suggested that granulomatous reaction is an important factor for this reduction in cytochrome P-450 and microso-ma1 enzyme level (1 5).…”
Section: Discussionsupporting
confidence: 91%
“…These inflammatory mediators released from granulomatous reaction inhibit the de novo synthesis of enzymes in the endoplasmic reticulum of the hepatocytes. This is consistent with previous work where BCG significantly reduced drug biotransformation in animals (14,15). Moreover, Farguhar et al suggested that granulomatous reaction is an important factor for this reduction in cytochrome P-450 and microso-ma1 enzyme level (1 5).…”
Section: Discussionsupporting
confidence: 91%